Analisis Praktik Menggendong pada Buruh Gendong Wanita di Pasar Induk Buah pada Sayur Giwangan Kota Yogyakarta - Hesti Meylia Pratiwi; Baju Widjasena; Suroto Suroto (Jurnal Kesehatan Masyarakat (Undip), 2015)
The manual manpower using is still not inevitable despite the development of the world's technology is already using devices automatically. One of them is the work of lifting and carrying properties manually. The survey has been conducted to report that 17.3 million people in the United Kingdom have experienced back pain. This amount of 1.1 million people experience paralysis due to back pain. The purpose of this research was to analyzed the cradling practicefor women carrying fruit and vegetable labour at the market Giwangan Yogyakarta City. This research was using qualitative research with descriptive analysis method with observation and in-depth interviews. The subjects of these studies amounted to 6 people as the main informant labours carrying. The results showed that the length of time working was more than 8 hours but the labours had the time to rest. Practice of carrying was not entirely correct in terms of technique of lifting weights. Load was transported in a single transport which had a range of 25 kg to 95 kg. The average frequency of freight per day conducted 8-25 times with a distance of approximately 1.776 metres in length was more than 2 hours. The attitude of the work being used was the working attitude of bending, lifting and carrying loads. In this study did not find any repetitive motion. The conclusion from this research was the holding practice of labours carrying still was not entirely correct and there should be improvement work. The suggestion for market managementwas to organizeda public awareness about the importance of safety in the workplace and providedpublic health facilities.